Correlation Between Intensity of Instagram Social Media User and Narcissism in Generation Z - Julia Putri Wandira; Imammul Insan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia ranks ninth out of ten countries with an average of 3 hours and 11 minutes of social media usage per day. The Z generation uses Instagram extensively. Generation Z uses this platform to update themselves and get praise from others. This study aims to find out the relationship between the intensity of social media use on Instagram and narcissism in Generation Z. This type of research involves quantitative correlation with a cluster sample consisting of 157 active psychology students at Sumbawa University of Technology. The results show a positive relationship between the two variables with a very strong coefficient value of 0.880, which indicates that the higher the intensity, the higher narcissism, and so is the other way